2013
DOI: 10.1186/1475-2875-12-302
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the efficacy of dihydroartemisinin with atorvastatin in an experimental cerebral malaria murine model

Abstract: BackgroundThe medical care of malaria is a clinical emergency because it may develop into severe malaria, which has a high risk of complications and death. One of the major complications of Plasmodium falciparum infections is cerebral malaria (CM), which is responsible for at least 175,000 deaths worldwide each year and has long-term neurological sequelae. Moreover, treatment for CM is only partially effective. Statins are now known to have anti-inflammatory action, to attenuate sepsis and to have neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…One research has shown that DHA could be liable to penetrate the brain-blood barrier (Xie et al, 2009). In addition, low doses of DHA have beneficial effects on brain diseases, for example, experimental cerebral malaria in mice (Dormoi et al, 2013). In the present study, we used DHA to treat APP/PS1 double transgenic AD mice and AD model cells, intending to investigate whether DHA would maintain Aβ related production and degradation balance via promoting autophagy flux and exert a protective effect in AD.…”
Section: Introductionmentioning
confidence: 98%
“…One research has shown that DHA could be liable to penetrate the brain-blood barrier (Xie et al, 2009). In addition, low doses of DHA have beneficial effects on brain diseases, for example, experimental cerebral malaria in mice (Dormoi et al, 2013). In the present study, we used DHA to treat APP/PS1 double transgenic AD mice and AD model cells, intending to investigate whether DHA would maintain Aβ related production and degradation balance via promoting autophagy flux and exert a protective effect in AD.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, combination of these 2 drugs has a synergistic effect, shorter course, and reduced drug dosage and toxicity [ 18 ]. The study of Jérôme Dormoi et al [ 19 ] also showed that atorvastatin in combination with dihydroartemisinin in a therapeutic scheme leads to a significant delay in mouse death, and it has an effect on the onset of cerebral malaria symptoms and on the level of parasitemia.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, signs of inflammation (increased pro-inflammatory cytokines and chemokines) and endothelial dysregulation become prominent. Under conditions where antimalarial treatment only partially reverses the course of illness, additional treatment with a statin (204)(205)(206) or another intervention (207,208) that affects endothelial cells reduces neuroinflammation, restores endothelial barrier integrity, and increases survival. Dysregulation of the Angpt/Tie2 signaling axis is also seen in experimental P. berghei infection (32,(209)(210)(211).…”
Section: Implications For Treating the Host Response To Other Acute Imentioning
confidence: 99%